Análise dos determinantes da taxa de juros para o segmento de pessoa jurídica e o papel de regulador econômico do Banco do Brasil - Rocha Sobrinho, Daniel (2021)
In Brazil, despite recent historical decreases in the basic rates of the economy, it was found that the average interest rates practiced in the Brazilian banking market remain high, especially when observing the market for micro, small and medium-sized companies. Thus, starting from a context where a highly concentrated sector, such as the banking sector, but with the relevant participation of a public bank, Banco do Brasil, the objective of this paper is to analyze the behavior of the main variables that influence the average interest rate practiced for the companies segment and verify, through estimation in an econometric model whether the allocation of the volume of credit aimed at the wholesale corporate segment (Large Companies) was entirely directed to the Micro, Small and Medium companies segment, could be an alternative to lower the rates currently practiced, via an increase of supply, reinforcing Banco do Brasil's role as economic regulator. For this purpose, data was collected from January 2012 to March 2021 on variables related to volume, default, macroeconomic aspects, in addition to the effect of the Corona Virus pandemic. Using an econometric multiple linear regression model of Ordinary Least Squares (MQO), it was possible to confirm that the increase in the supply of credit, by itself, is capable of decreasing the average rate charged by banks for Legal Entities. Thus, if Banco do Brasil adopted a policy to expand credit to Micro, Small and Medium-sized companies, by a strategic decision for exclusivity of operation with this segment, without the need for artificial interference in rates, it could influence the reduction of rates practiced by the banking market, thus acting as an economic regulator.